Frequency of Dentine Hypersensitivity and their Associated Risk Factors Amongst the Patients Visiting the Dental Outpatient Department - Akhtar Zeb, Shandana Amirzadah, Fawad Ahmad, Fatima Afridi, Nahmeed Ullah, Akhtar Munir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Medical practitioners often encounter dentine hypersensitivity, which is a challenging problem to manage. Dentine hypersensitivity is characterized by acute, transient discomfort from an exposed dentin region in response to stimuli that is unrelated to any other disease. Objective: To assess the frequency of dentine hypersensitivity and their associated risk factors amongst the patients visiting the dental outpatient department Methodology: The current study was cross-sectional, carried out at the dental outpatient department of Qazi Hussain Ahmad Medical Complex, Nowshera for duration of six months from January 2022 to June 2022. The survey questionnaire included queries about patient’s age, gender, dentine hypersensitivity presence/absence awareness and factors associated with the dentine hypersensitivity. Data analysis was carried out by using IBM SPSS version 23. Results: The overall frequency of dentine hypersensitivity was observed in 98 (35%) patients. Based on gender, dentine hypersensitivity was observed in 35 (27.77%) males and 63 (40.90%) females. The major risk factors of tooth sensitivity were ice cream in 118 (42.14%) participants followed by iced water in 64 (22.86%) participants. Practical implication: There is little information available in Pakistan on how much the general public is familiar of dentine hypersensitivity. Therefore, this study will help to determine the prevalence of dentine hypersensitivity amongst patients who visited the dental outpatient clinic at the Qazi Hussain Ahmad Medical Complex in Nowshera and to analyze the various risk factors associated with it. Conclusion: Our study concludes that dentine hypersensitivity is highly prevalent in patients visiting the dental outpatients department. Dentine hypersensitivity was frequently observed in females as compared to males. Ice cream and iced water were the major risk factors in our study. Keywords: Dentine hypersensitivity; Frequency; Outpatient department; Risk factors